(untitled) (Homoeopathy for All, 2022)
Acidity is one of the most common presenting complaint at clinics/ hospitals and almost everyone has experienced acidity at least once in their lifetime. Acidity occurs due to multiple different mechanisms that can be intrinsic, structural, or both, leading to the disruption of the esophago-gastric junction barrier resulting in exposure of the esophagus to acidic gastric contents which causes discomfort and symptoms like heartburn, sore throat, regurgitation, dysphagia etc. Acidity can result from a variety of physiological/ pathological and behavioral causes. This article aims to discuss the epidemiology, etiology, symptomatology, differential diagnosis and homoeopathic management of acidity.